Singing the Land : Hebrew Music and Early Zionism in America - Sperling, Eli (Book collections on Project MUSE., 2024)
Singing the Land: Hebrew Music and Early Zionism in America examines the proliferation and use of popular Hebrew Zionist music amongst American Jewry during the first half of the twentieth century. This music--one part in a greater process of instilling diasporic Zionism in American Jewish communities--represents an early and underexplored means of fostering mainstream American Jewish engagement with the Jewish state and Hebrew national culture as they emerged after Israel declared its independence in 1948. This evolutionary process brought Zionism from being an often-polemical notion in American Judaism at the turn of the twentieth century to a mainstream component of American Jewish life by 1948. Hebrew music ultimately emerged as an important means through which many American Jews physically participated in or 'performed' aspects of Zionism and Hebrew national culture from afar. Exploring the history, events, contexts, and tensions that comprised what may be termed the 'Zionization' of American Jewry during the first half of the twentieth century, Eli Sperling analyzes primary sources within the historical contexts of Zionist national development and American Jewish life. Singing the Land offers insights into how and why musical frameworks were central to catalyzing American Jewry's support of the Zionist cause by the 1940s, parallel to firm commitments to their American locale and national identities. The proliferation of this widespread American Jewish-Zionist embrace was achieved through a variety of educational, religious, economic, and political efforts, and Hebrew music was a thread consistent amongst them all.